2021
DOI: 10.3168/jds.2020-19344
|View full text |Cite
|
Sign up to set email alerts
|

Association of subclinical hypocalcemia dynamics with dry matter intake, milk yield, and blood minerals during the periparturient period

Abstract: Subclinical hypocalcemia (SCH) affects many highproducing dairy cows in the postpartum period. Recent work has shown that cows experiencing prolonged or delayed SCH are at increased risk for disease and produce less milk than cows experiencing a transient reduction in or normal concentrations of plasma Ca following parturition. Our objective was to determine the association between different postpartum SCH dynamics with preand postpartum dry matter intake (DMI), milk yield, and blood mineral concentrations. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 35 publications
2
22
0
1
Order By: Relevance
“…Nevertheless, as our study included only 2 herds, the external applicability of our results is limited and research including a larger number of herds is needed. Furthermore, recent research suggests that postpartum blood Ca dynamics (persistent, transitory, delayed) is what determines future productive performance rather than a single blood Ca assessment as performed in the present study (McArt and Neves, 2020;Seely et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Nevertheless, as our study included only 2 herds, the external applicability of our results is limited and research including a larger number of herds is needed. Furthermore, recent research suggests that postpartum blood Ca dynamics (persistent, transitory, delayed) is what determines future productive performance rather than a single blood Ca assessment as performed in the present study (McArt and Neves, 2020;Seely et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
“…But later, as proposed by Neves (2020) andCouto Serrenho et al (2021), low blood Ca concentration could indicate cows' inability to adapt to increased Ca demands, or reflect lower feed intake, inflammation, or disease. In a recent study, Seely et al (2021) observed that cows with persistent (Ca ≤1.95 at 1 DIM and ≤2.20 mmol/L at 4 DIM) and delayed (Ca ≤2.2 mmol/L at 4 DIM) subclinical hypocalcemia had statistically and numerically lower DMI, respectively, compared with normocalcemic cows. Only Østergaard and Larsen (2000) reported ECM yield, which, contrary to our findings, was not associated with plasma Ca concentration assessed within 12 h postpartum.…”
Section: Discussionmentioning
confidence: 96%
“…However, no significant differences were detected between treatments. These results are unsurprising, considering that this experiment was not powered to analyze milk yield, but they pose interesting consideration when discussing blood calcium, DMI, and milk yield in the current study, as transient hypocalcemia in the immediate days postpartum has been associated with increased milk production when compared with normocalcemic cows (McArt and Neves, 2020), despite a lack of change in DMI (Seely et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
“…The major criticism is the lack of a clear PTH threshold for both calcium and vitamin D supplementation. Some authors suggest that PTH may not be the only determinant for the development of hypocalcemia and that other factors may play a major role such as vitamin D deficiency [40], dietary habits [41], and other metabolic disorders such as hypomagnesemia [42,43]. Hypomagnesemia is frequently associated with the use of drugs such as aminoglycosides, cyclosporine, cisplatin, amphotericin B, ACE inhibitors, proton pump inhibitors, and some diuretics (thiazides and loop) [44].…”
Section: Discussionmentioning
confidence: 99%